SynBio in 3D: The first synthetic genetic circuit as a 3D printed STEM educational resource - Oss Boll, Heloísa; de Castro Leitão, Matheus; Garay, Aisel Valle; Batista, Ana Carolina Campos; de Resende, Sophia Garcia; da Silva, Leonardo Ferreira; Reis, Viviane Castelo Branco; Vieira, Emerson Monteiro; Coelho, Cíntia Marques (Frontiers in Education, 2023)
Synthetic biology is a new area of science that operates at the intersection of engineering and biology and aims to design and synthesize living organisms and systems to perform new or improved functions. Despite the important role it plays in resolving global issues, instructing synthetic biology can be challenged by a limited availability of specific educational materials and techniques for explaining complex molecular mechanisms. On the other hand, digital fabrication tools, which allow the creation of 3D objects, are increasingly used for educational purposes, and several computational structures of molecular components commonly used in synthetic biology processes are deposited in open databases. Therefore, we hypothesized that the use of computer-assisted design (CAD) and 3D printing to create biomolecular structural models through hands-on interaction, followed by reflective observation, critical and analytical thinking, could enhance students' learning in synthetic biology. In this sense, the present work describes the design, 3D printing process, and evaluation in classrooms of the molecular models of the first synthetic biological circuit, the genetic toggle switch. The 3D printed molecular structures can be freely downloaded and used by teachers to facilitate the training of STEM students in synthetic biology. Most importantly, the results demonstrated that our resource showed a significant positive impact (p < 0.05) on students’ learning process, indicating that the proposed method helped them better understand the genetic toggle switch.